Anthropogenic Overdevelopment and Ecological Apocalypse in Richard Adams’ Watership Down - Nanda Resya Afrizal; Henrikus Joko Yulianto (Universitas Islam Negeri Palopo, 2026)
Watership Down by Richard Adams depicts a rabbit community confronted with ecological damage caused by human intrusion. While the work is commonly understood as an adventure or animal story, this study focuses on its representation of ecocide and its implications for rabbit survival. Drawing on Franz Broswimmer's theory of ecocide, the study investigates how human overdevelopment disturbs rabbit habitat, displaces groups, threatens social harmony, and makes animals more vulnerable. The study uses a qualitative approach, doing a close textual analysis of chosen events in the novel to trace the impact of environmental damage on rabbit life. The findings show that anthropogenic environmental damage causes habitat destruction, displacement, societal breakdown, and mass loss. According to the study, the novel portrays ecocide as both an ecological and ethical dilemma. It contributes to ecocriticism and environmental humanities by providing a literary examination of the link between human expansion, ecological collapse, and nonhuman survival.